Experimental freezing of freshwater pennate diatoms from polar habitats - Hejduková, Eva; Nedbalová, Linda (Protoplasma, 2021)
Diatoms are microalgae that thrive in a range of habitats worldwide including polar areas. Remarkably, non-marine pennate diatoms do not create any morphologically distinct dormant stages that could help them to successfully face unfavourable conditions. Their survival is probably connected with the adaptation of vegetative cells to freezing and desiccation. Here we assessed the freezing tolerance of vegetative cells and vegetative-looking resting cells of 12 freshwater strains of benthic pennate diatoms isolated from polar habitats. To test the effect of various environmental factors, the strains were exposed to -20 °C freezing in four differently treated cultures: (1) vegetative cells growing in standard conditions in standard WC medium and (2) resting cells induced by cold and dark acclimation and resting cells, where (3) phosphorus or (4) nitrogen deficiency were used in addition to cold and dark acclimation. Tolerance was evaluated by measurement of basal cell fluorescence of chlorophyll and determination of physiological cell status using a multiparameter fluorescent staining. Four strains out of 12 were able to tolerate freezing in at least some of the treatments. The minority of cells appeared to be active immediately after thawing process, while most cells were inactive, injured or dead. Overall, the results showed a high sensitivity of vegetative and resting cells to freezing stress among strains originating from polar areas. However, the importance of resting cells for survival was emphasized by a slight but statistically significant increase of freezing tolerance of nutrient-depleted cells. Low numbers of surviving cells in our experimental setup could indicate their importance for the overwintering of diatom populations in harsh polar conditions.
Keywords: Chlorophyll; sladká voda; Freezing tolerance; Diatoms; Polar regions; zmrazování; chlorofyl; Resting cells; Stress survival; Fresh Water; Viability; rozsivky; Freezing; ekosystém; Ecosystem